IKBKE activity enhances AR levels in advanced prostate cancer via modulation of the Hippo pathway. Issue 10 (23rd April 2020) - Bainbridge, Alex; Walker, Scott; Smith, Joseph; Patterson, Kathryn; Dutt, Aparna; Ng, Yi Min; Thomas, Huw D; Wilson, Laura; McCullough, Benjamin; Jones, Dominic; Maan, Arussa; Banks, Peter; et al.
Abstract: Resistance to androgen receptor (AR) targeting therapeutics in prostate cancer (PC) is a significant clinical problem. Mechanisms by which this is accomplished include AR amplification and expression of AR splice variants, demonstrating that AR remains a key therapeutic target in advanced disease. For the first time we show that IKBKE drives AR signalling in advanced PC. Significant inhibition of AR regulated gene expression was observed upon siRNA-mediated IKBKE depletion or pharmacological inhibition due to inhibited AR gene expression in multiple cell line models including a LNCaP derivative cell line resistant to the anti-androgen, enzalutamide (LNCaP-EnzR). Phenotypically, this resulted in significant inhibition of proliferation, migration and colony forming ability suggesting that targeting IKBKE could circumvent resistance to AR targeting therapies. Indeed, pharmacological inhibition in the CWR22Rv1 xenograft mouse model reduced tumour size and enhanced survival. Critically, this was validated in patient-derived explants where enzymatic inactivation of IKBKE reduced cell proliferation and AR expression. Mechanistically, we provide evidence that IKBKE regulates AR levels via Hippo pathway inhibition to reduce c-MYC levels at cis -regulatory elements within the AR gene. Thus, IKBKE is a therapeutic target in advanced PC suggesting repurposing of clinically tested IKBKE inhibitors could be beneficial to castrate resistant PC patients.